Patients with Ankylosing Spondylitis and Low Disease Activity because of Anti-TNF-Alpha Therapy Have Higher TRAIL Levels Than Controls: A Potential Compensatory Effect. (21st May 2014) - Genre, Fernanda; López-Mejías, Raquel; Rueda-Gotor, Javier; Miranda-Filloy, José A.; Ubilla, Begoña; Carnero-López, Beatriz; Palmou-Fontana, Natalia; Gómez-Acebo, Inés; Blanco, Ricardo; Pina, Trinitario; Ochoa, Rodrigo; González-Juanatey, Carlos; et al.
Abstract : Objective . TRAIL is a potential biomarker of cardiovascular (CV) disease. Ankylosing spondylitis (AS) is a chronic inflammatory disease associated with metabolic syndrome (MeS) and accelerated atherosclerosis. We assessed whether disease activity, systemic inflammation, and MeS features were associated with circulating TRAIL levels in AS patients undergoing TNF- α antagonist infliximab therapy and if infliximab infusion modified TRAIL levels. Methods . We measured TRAIL serum levels in 30 nondiabetic AS patients without CV disease undergoing anti-TNF- α therapy, immediately before and after an infliximab infusion, and in 48 matched controls. Correlations of TRAIL levels with disease activity, systemic inflammation and MeS features, adipokines, and biomarkers of endothelial activation were evaluated. Changes in TRAIL levels following anti-TNF- α infusion were analyzed. Results . TRAIL levels were higher in AS patients than controls. TRAIL levels displayed an inverse correlation with total and LDL cholesterol. We observed an inverse correlation with QUICKI and a marginal association with HOMA-IR. We also found an inverse correlation with resistin and a marginal association with apelin and OPN. Anti-TNF- α infusion did not change TRAIL levels after 120′. Conclusion . Elevated TRAIL levels in AS patients may be the result of a compensatory mechanism to reduce CV risk in these patients.